The Effect of Antimicrobial Photodynamic Therapy with Radachlorin® on Staphylococcus Aureus and Escherichia Coli: An in Vitro Study - Fekrazad, Reza; Zare, Hadi; Mohammadi Sepahvand, Sara; Morsali, Parisa (Journal of Lasers in Medical Sciences, 2014)
Introduction: The aim of this study is the evaluation of the effect of Antimicrobial Photodynamic Therapy with Radachlorin on Staphylococcus aureus and Escherichia coli. New windows are open in the antimicrobial field so-call Photodynamic therapy that incorporates a nonpoisonous photosensitizer (PS) with innocuous special wavelength photons to excite the PS. Methods: Two strains of bacteria used in this study were Methicillin resistant Staphylococcus aureus (ATCC 33591; PTCC 1764) and Escherichia coli (ATCC 25922; PTCC1399). Concentrations of 0.2 ml of Radachlorin® were applied on 0.2 ml of bacterial suspensions and placed in a 48-well microtiter plate. The following groups were used: (I) L− PS− (no laser, no photosensitizer), (II) L−PS+ (treated only with PS), (III) L+ PS− (treated only with laser) and (IV) L+ PS+ (treated with laser and PS: photodynamic therapy group). Aliquots of bacterial suspensions were sensitized with Radachlorin® for 15 minutes in the dark at room temperature and then bacterial suspensions in group III and IV were irradiated with 210 mW (power density) and 12 J/cm2 (energy density) on continuous mode. Results: This study showed that photodynamic therapy reduces 0.14 log 10 in E.Coli (group IV) and there were significant differences for group IV (P<0.01). Photodynamic therapy in S.Aureus showed 6.28 log 10 colony count reduction (group IV) and there were highly significant differences in Photodynamic therapy group (P<0.0001). Conclusion: Radachlorin® have bactericidal effect on S.aureus (6.28 log 10) and bacteriostatic effect on E.coli (0.14 log 10).